Concepciones de los alumnos de 15-18 años sobre la estructura interna de la mateiral en el estado sólido - Posada, José María de (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
A questionary of free answers has been used in order to elicit pupils' ideas about the internal structure of some substances. The 15-16 years old pupils (22 de SUP) use an atomic framework with a gas and a non atomics one with solids. The differences between melting points are explained by pupils using macroscopic reasonings, atomic arguments, or mixting both of them.